2021
DOI: 10.1186/s13063-021-05926-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral intake of royal jelly on endothelium function in hemodialysis patients: study protocol for multicenter, double-blind, randomized control trial

Abstract: Background Hemodialysis (HD) is a common renal replacement therapy for patients with renal failure. Cardiovascular and cerebrovascular diseases are known to shorten survival periods and worsen the quality of life of HD patients. Atherosclerosis is a major cause of vascular diseases, and various factors such as abnormality of lipid metabolism and increased macrophage activity, oxidative stress, and endothelial dysfunction are associated with its pathogenesis and progression. Further, endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…At the clinical level, a randomized, placebo-controlled study demonstrated that a daily intake of RJ tablets (690 mg) for four weeks significantly improved the vascular endothelial activity of the participants' blood vessels, suggesting that RJ may exert antiatherogenic activity [106]. Another clinical study reported that the treatment of renal failure patients suffering from cardiovascular disease with a daily dosage of RJ (3600 mg) for a year considerably attenuated the progression of atherosclerosis in hemodialysis patients [15]. Figure 5 illustrates the mechanism of the antihypertensive activity of RJ.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the clinical level, a randomized, placebo-controlled study demonstrated that a daily intake of RJ tablets (690 mg) for four weeks significantly improved the vascular endothelial activity of the participants' blood vessels, suggesting that RJ may exert antiatherogenic activity [106]. Another clinical study reported that the treatment of renal failure patients suffering from cardiovascular disease with a daily dosage of RJ (3600 mg) for a year considerably attenuated the progression of atherosclerosis in hemodialysis patients [15]. Figure 5 illustrates the mechanism of the antihypertensive activity of RJ.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Royal jelly (RJ) is a "rich source of nutrients" that nurse bees produce and feed to worker larvae and queen bees. RJ supplementation is beneficial for a variety of disorders, including diabetes [11,12], gastrointestinal diseases [13,14], and cardiovascular diseases [15,16]. The active ingredients of RJ, including its proteins, carbohydrates, and fats, as well as its minerals, amino acids, vitamins, enzymes, hormones, and polyphenols, are what provide its biological properties [17].…”
Section: Introductionmentioning
confidence: 99%